SASTRA LISAN TANDUK MASYARAKAT GENAHARJO KABUPATEN TUBAN: PERSPEKTIF STRUKTUR NARATIF, MAKNA, DAN FUNGSI SOSIAL BAGI MASYARAKAT PENDUKUNGNYA - Suantoko (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This study aims to understand the narrative structure tanduk oral literature. In addition, it aims to understand the meaning and social function of the oral literature for the local community. The results showed formulas and formulaic expressions of oral literature tanduk is formula and formula syntax reps. The handyman tanduk does not need to memorize the formulaic expressions. They just watched offerings in front of him. Inheritance procedure is not through formal education in particular. Philosophical meaning tanduk oral literature that is safety and attitude towards God, mankind and the universe. Social functions contained in the oral literature is the function of propaganda, social interaction function, the function of education in the socialization of social values, and an antidote to individualism.